Maslahah-Based Institutional Mediation in Civil Servant Divorce: The Role of the Personnel Development Division at the Lampung High Prosecutor’s Office - Yayan Indriana (Universitas Islam Negeri Raden Intan Lampung, 2026)
The core problem of this study is weak protection of child victims of sexual violence when the perpetrator is the holder of parental authority or guardianship, requiring state intervention through the State Attorney. This study aims to analyze the authority, legal considerations, and practice of the State Attorney in revoking guardianship rights of child victims of sexual violence in Lampung Province. The theoretical framework combines maslahah mursalah and law as a tool for social engineering to examine child protection as public benefit and as an instrument of social transformation. This research uses a qualitative approach with field research supported by library research. Primary data were obtained through interviews with State Attorneys, observation, documentation, and three Religious Court decisions: Decision Number 312/Pdt.G/2023/PA.Prw, 593/Pdt.G/2024/PA.Gdt, and 411/Pdt.G/2024/PA.Kr. Secondary data were collected from legislation, Islamic family law literature, child protection law, and scholarly articles. The findings show that the State Attorney has legal standing to petition for revocation of guardianship in the best interests of the child. Judges considered criminal facts, psychological trauma, the biological father’s unfitness as guardian, legal norms, and the principle of public benefit. The three decisions revoked the perpetrators’ parental authority and appointed the biological mothers as substitute guardians. This study recommends inter-institutional technical guidelines, strengthening State Attorney capacity, and continuing psychosocial assistance so court decisions ensure recovery, safe care, and prevention of repeated violence.